Survey of community residents as a basis for forming a strategic long-term purpose for community development - Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2020)
This article analyzes the strategies that are being developed for the communities, identifies whether they can lead to economic and social development of the community and increase budget revenues in the long run. It is found that the most important part, the most powerful resource of a community is its people. In the course of the research, it was decided to conduct a qualitative and quantitative survey of the residents of Kolomatska UTC using the method of anonymous online questionnaire using the Google Docs service. There is a high level of awareness among the residents of the community on the issues of decentralization of power, as well as the positive impact of decentralization on the development of the community. It is determined that 63% of the surveyed residents of the community positively evaluate the prospect of further life in the community and do not plan to leave it. The survey found that about half of those surveyed were willing to work with fellow villagers in co-operative societies or production associations to improve their work efficiency and increase their own well-being and community development. It was also found that the vast majority wanted to learn new skills and do it on their own. The result of this research is the formation of a strategic goal of community development for a long period. Keywords: regional development, decentralization, community development strategy, polls, questionnaires, online questionnaires, cooperation